Exacerbations of asthma following step-up and step-down inhaled corticosteroid and long acting beta agonist therapy in the managing asthma in pregnancy study. (1st February 2022) - Murphy, Vanessa E.; Jensen, Megan E.; Gibson, Peter G.
Abstract: Objective: Guidelines for asthma management contain a consensus recommendation that inhaled corticosteroid (ICS) dose should not be stepped down in pregnancy. However, this is not consistent with consumer preferences and pharmacological principles to minimize medication exposure during pregnancy. We investigated exacerbations after changes to ICS and long acting beta agonist (LABA) therapy in pregnant women with asthma. Methods: Pregnant women ( n  = 220) were recruited to a randomized controlled trial (RCT) where maintenance treatment was adjusted monthly based on either symptoms (control group), or fractional exhaled nitric oxide (FeNO, to alter ICS) and symptoms (to alter LABA, FeNO group). Exacerbations were monitored prospectively. Results: ICS were used by 137 (62.3%) women at some time during pregnancy. ICS dose remained unchanged in 16 women (11.7%, 95% confidence interval [CI] 7–18%), increased in 37 women (27%, 95%CI 20–35%), decreased in 34 women (24.8%, 95%CI 18%–33%), or both increased and decreased in 50 women (36.5%, 95%CI 29–45%). Exacerbations occurred within 14 days of ICS step-down in 11 women (13%, 95%CI 7.5%–22%). This was not significantly different from exacerbations occurring within 14 days of step-up, in 7 women (8.1%, 95%CI 4%–16%, P  = 0.294). There were no differences between management groups. Exacerbations occurred within 14 days of step-down in 14.7% (95%CI 7%–30%) of women in the control group, and in 12% (95%CI 6%–24%) of women in the FENO group. Conclusions: ICS step-down could be considered when eosinophilic inflammation or symptoms are low, and may be a useful management approach for women, doctors, and midwives wishing to minimize ICS exposure during pregnancy.